2023
DOI: 10.1101/2023.02.02.526850
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetically Defined Subtypes of Somatostatin-Containing Cortical Interneurons

Abstract: Of the four main subclasses of inhibitory cortical interneurons, somatostatin-containing (SOM) interneurons are the most diverse. Earlier studies identified layer 1-projecting (Martinotti) cells in layer 5/6 of the X98 and the Chrna2-cre transgenic lines, and two groups of non-Martinotti cells - long-range projecting SOM cells in layers 2 and 6, and layer 4-projecting X94 cells in layers 4 and 5. Later in-vivo and ex-vivo studies described two morphological types of Martinotti cells which appear to have opposi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 139 publications
0
5
0
Order By: Relevance
“…Observed complementary networks of inhibition (L4 vs L5) Sst+ cells in L4 and 5 with distinct axonal morphology have distinct intrinsic physiology 21,69 and even opposite behavior during whisking 37 . Some studies found that Sst cells specifically innervate excitatory targets in one layer but not the other (Sst+ cells innervating L4 will target L4 and not L5 pyramidal cells and vice versa) 32,38,39 .…”
Section: Integrated View Of Met-types and Connectivitymentioning
confidence: 99%
“…Observed complementary networks of inhibition (L4 vs L5) Sst+ cells in L4 and 5 with distinct axonal morphology have distinct intrinsic physiology 21,69 and even opposite behavior during whisking 37 . Some studies found that Sst cells specifically innervate excitatory targets in one layer but not the other (Sst+ cells innervating L4 will target L4 and not L5 pyramidal cells and vice versa) 32,38,39 .…”
Section: Integrated View Of Met-types and Connectivitymentioning
confidence: 99%
“…3C, left, many trends immediately pop out: PV + cells seem to be uniformly narrow no matter the layer; SOM + cells occupy a gradient of widths and overlap with E-5 cells at their widest; and the widest spiking cells are E-4. This finding regarding SOM + cells occupying a range of spike widths is likely because it is composed of several subtypes of varying widths (Hostetler et al, 2023) which have distinct computational roles (Wu et al, 2023). Waveform peak-to-trough ratios also differ between cell types Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Again, as in the juxtacellular dataset, the PhysMAP approach provided interpretable representations. To illustrate this point, we identified two sub-populations of SOM + cells not documented in the original publication of this dataset (Lakunina et al, 2020) but predicted by the literature (Hostetler et al, 2023; Wu et al, 2023; Urban-Ciecko and Barth, 2016). These wide-spiking SOM + (WS-SOM + , Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations